Identification and characterization of two novel viruses in ocular infections in reindeer. - Saskia L Smits (Public Library of Science (PLoS), 2013)
A thorough understanding of virus diversity in wildlife provides epidemiological baseline information about pathogens. In this study, eye swab samples were obtained from semi-domesticated reindeer (Rangifertarandus tarandus) in Norway during an outbreak of infectious eye disease, possibly a very early stage of infectious keratoconjunctivitis (IKC). Large scale molecular virus screening, based on host nucleic acid depletion, sequence-independent amplification and next-generation sequencing of partially purified viral nucleic acid, revealed the presence of a new papillomavirus in 2 out of 8 eye swab samples and a new betaherpesvirus in 3 out of 8 eye swab samples collected from animals with clinical signs and not in similar samples in 9 animals without clinical signs. Whether either virus was responsible for causing the clinical signs or in any respect was associated to the disease condition remains to be determined.